The Effect of Calcium Hydroxide on Fibroblast Cells Viability - Vincentia Adya Paramitta; Tetiana Haniastuti Heni; Susilowati Susilowati (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
Calcium hydroxide [Ca(OH)2] is widely used as medicament in dental pulp and root canal therapy. Previous studies demonstrate the ability of calcium hydroxide to induce necrosis in dental pulp tissue. However, the mechanism of tissue destruction remains unknown. The aim of this study was to investigate fibroblast cell viability in response to calcium hydroxide exposure. In this study, Vero fibroblast cell line was treated with various concentrations of calcium hydroxide for 24 hours. Cell viability was measured by using MTT assay. Our results showed significant decrease in cell viability after exposed with calcium hydroxide at concentration 62.5 and 125 µg/ml. The result indicated that calcium hydroxide induced cell death in Vero cell line in a dosedependent manner. This study suggests that fibroblast cell death may involved in the mechanism of pulp tissue necrosis caused by calcium hydroxide